Evaluation of efficiency of Wheat straw nanocellulose as nanoadsorbent for the removal of divalent copper, lead and zinc from aqueous solution - Mandeep Kaur; Jitender Pal (Carbohydrate Polymer Technologies and Applications, 2023)
Novel nanocellulose (cellulosic carbohydrate polymer) embedded with Wheat straw was synthesized, characterized and examined as nanoadsorbent for the removal of copper, lead and zinc metals from aqueous solution through batch mode. The effects of pH, dose, contact time, temperature and synchronous cations on the amount of Cu (II), Pb (II) and Zn (II) adsorbed have been probed. The desirable pH was 8 and nanoadsorbent dose was 0.6 g/50 mL in the adsorption study. The removal efficiencies of Cu (II), Pb (II) and Zn (II) were 88.75%, 81.18%, 86.84% respectively. Adsorption kinetic study was employed to analyze experimental data and adsorption process followed pseudo second order kinetic model. Langmuir, Freundlich, Temkin and Redlich-Peterson isotherm models were used to indicate the adsorption of Cu (II), Pb (II) and Zn (II) on WSN and thermodynamic study affirmed that adsorption process was endothermic and spontaneous. AFM indicated size and morphology and attachment of functional groups on WSN were examined by FTIR. The results confided that adsorption is economically competent method for removing Cu (II), Pb (II) and Zn (II) and WSN is anticipative owing to its ease and low cost of regeneration